Topographical Anatomy Of The Profunda Femoris Artery And The Femoral Nerve: Normal And Abnormal Relationship. - K.W. Choy; S. Kogilavani; M. Norshalizah; S. Rani,; A. Aspalilah; H. Hamzi; H.S. Farihah; S. Das (La clinica terapeutica, 2024)
Volume :164